BELAJAR ISLAM LEWAT MEDIA SOSIAL: MENGUKUR PENGARUH MEDIA SOSIAL TERHADAP PEMAHAMAN KEISLAMAN MAHASISWA UNIMED - Dwi Susanti; Dwi Atika Zahara; Siti Mardiah; Hapni Laila Sirega; Khairiah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
Currently, digital platforms such as Instagram, YouTube, and TikTok have become the main means for students to access, disseminate, and discuss religious information quickly and interactively. Social media presents Islamic content that is engaging, easily accessible, and packaged in a visual format that aligns with the preferences of the younger generation, who tend to favor concise and audiovisual information. This study aims to examine the extent to which the use of social media by students at Universitas Negeri Medan affects their understanding of Islamic teachings. The research was conducted using an associative quantitative approach, employing a questionnaire distributed online via Google Forms to measure the impact of social media usage on students' understanding of Islam. The number of respondents involved was 39 students from various majors and faculties. The results of the data analysis using simple linear regression show that social media usage has a positive and significant impact on Islamic understanding among students, as evidenced by a t-value of 3.509, which is greater than the t-table value of 2.0262, and a significance value of 0.001, which is less than 0.05. These findings reinforce that social media has a significant contribution to enhancing the understanding of Islam among students at Universitas Negeri Medan.